2005
DOI: 10.1158/1078-0432.ccr-04-1785
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Chemoresistance to Gemcitabine Is Associated with Decreased Expression of BNIP3 in Pancreatic Cancer

Abstract: Purpose: Although chemotherapy with gemcitabine is a common mode of treatment of pancreatic cancer, 75% of patients do not benefit from this therapy. It is likely that the sensitivity of cancer cells to gemcitabine is determined by a number of different factors. Experimental Design: To identify genes that might contribute to resistance to gemcitabine, 15 pancreatic cancer cell lines were subjected to gemcitabine treatment. Simultaneously, gene expression profiling using a cDNA microarray to identify genes resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(104 citation statements)
references
References 42 publications
5
99
0
Order By: Relevance
“…BNIP3 has long been regarded as a pro-apoptotic Bcl-2 family member (reviewed in Lee and Paik (2006) and Burton and Gibson (2009)). Silencing of BNIP3 correlates to increased pancreatic and colon tumour cell survival in vitro, and tumour progression, chemoresistance and worsened prognosis in vivo (de Angelis et al, 2004;Okami et al, 2004;Akada et al, 2005;Erkan et al, 2005;Bacon et al, 2007;Ishiguro et al, 2007;Mahon et al, 2007). Notably, these are two of the tumour types in which SIM2s is found to be aberrantly up-regulated (DeYoung et al, 2002(DeYoung et al, , 2003a.…”
Section: Identification Of Bnip3 As a Putative Target Of Repression Bmentioning
confidence: 99%
“…BNIP3 has long been regarded as a pro-apoptotic Bcl-2 family member (reviewed in Lee and Paik (2006) and Burton and Gibson (2009)). Silencing of BNIP3 correlates to increased pancreatic and colon tumour cell survival in vitro, and tumour progression, chemoresistance and worsened prognosis in vivo (de Angelis et al, 2004;Okami et al, 2004;Akada et al, 2005;Erkan et al, 2005;Bacon et al, 2007;Ishiguro et al, 2007;Mahon et al, 2007). Notably, these are two of the tumour types in which SIM2s is found to be aberrantly up-regulated (DeYoung et al, 2002(DeYoung et al, , 2003a.…”
Section: Identification Of Bnip3 As a Putative Target Of Repression Bmentioning
confidence: 99%
“…The promoter of BNIP3 is located within a CpG island and is methylated in most pancreatic cancer cell lines (Abe et al, 2005;Akada et al, 2005;Erkan et al, 2005). Restoration of BNIP3 expression by the methyltransferase inhibitor, 5-aza-2-deoxycytidine, leads to the death of pancreatic cancer cells in response to hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that HIF-1α induces both pro-apoptotic (BNIP3, NOXA, NIX, RTP801) and anti-apoptotic (FOXO3, IAP-2 and survivin) genes (19)(20)(21)(22)(23). For each cellular phenotype, the death or survival induced by hypoxia seems to depend on degree.…”
Section: Discussionmentioning
confidence: 94%